'What Do You Mean, You Are a Refugee in Your Own Country?': Displaced Scholars and Identities in Embattled Ukraine. Issue 2 (3rd April 2021) - Oleksiyenko, Anatoly; Terepyshchyi, Serhii; Gomilko, Olga; Svyrydenko, Denys
ABSTRACT: The concept of a 'displaced academic', which previously appeared in the analysis of the WWII-related forced migration from the Nazi-occupied Europe, has resurfaced in Ukraine's higher education after Russia's annexation of Crimea and invasion of the Donbas in 2014. We re-examine the relevance and interpretations of this concept in embattled Ukraine. Having interviewed 12 academics who fled the invaded territory, we seek to advance the theory of academic vulnerability in the context of geopolitical and cross-cultural divergences in the discordant post-Soviet space. Distinguished by its contextual analysis, this paper also expands the reader's understanding of forced migration in a disintegrating higher education space.